STRUCTURAL AND SEMANTIC FEATURES OF JARGON IN THE ENGLISH AND UZBEK LANGUAGES - Ravshanovich, O‘rinov Rustambek (Research Focus International Scientific Journal, 2026)
This article provides a comparative analysis of the structural and semantic characteristics of jargon in the English and Uzbek languages. It explores the methods of jargon formation, their functional roles in speech, and their connection with social factors. The results of the study help to determine the place of jargon within the lexical systems of the two languages.